Supplemental Insulin-Like Growth Factor-1 and Necrotizing Enterocolitis in Preterm Pigs - Holgersen, Kristine; Gao, Xiaoyan; Narayanan, Rangaraj; Gaur, Tripti; Carey, Galen; Barton, Norman; Pan, Xiaoyu; Muk, Tik; Thymann, Thomas; Sangild, Per Torp (Frontiers in Pediatrics, 2021)
Background: Recombinant human IGF-1/binding protein-3 (rhIGF-1/BP-3) is currently tested as a therapy in preterm infants but possible effects on the gut, including necrotizing enterocolitis (NEC), have not been tested. Using NEC-sensitive preterm pigs as a model for preterm infants, we hypothesized that rhIGF-1/BP-3 supplementation in the first days after birth would not negatively affect clinical variables, gut maturation or NEC. Methods: Preterm pigs were given twice daily subcutaneous injections of rhIGF-1/BP-3 or vehicle. Blood was collected for IGF-1 measurements and gut tissue for NEC evaluation and biochemical analyses on day 5. Results: Baseline circulating IGF-1 levels were low in preterm pigs compared with near-term pigs reared by their sow (<20 vs. 70 ng/mL). rhIGF-1/BP-3 treated pigs showed increased plasma IGF-1 levels for up to six hours after injection (>40 mg/mL). rhIGF-1/BP-3 treatment reduced the incidence of severe NEC lesions (7/24 vs.16/24, p=0.01) and overall NEC severity (1.8±0.2 vs. 2.6±0.3, p<0.05, most lesions in colon). In the small intestine, villi length (405±25 vs. 345±33 µm, p<0.05) and brush border peptidase activities (+31-53%, p=0.01-0.08) were increased by rhIGF-1/BP-3 relative to control pigs. The treatment had no effects on body weight, blood chemistry or hematology, except for an increase in blood leucocyte and neutrophil counts (p<0.05, i.e. reduced neonatal neutropenia). Likewise, rhIGF-1/BP-3 treatment did not affect intestinal tissue cytokine levels (IL-1β, IL-6, IL-8, TNFα,), enterocyte proliferation, goblet cell density, permeability or bacterial translocation to the bone marrow. Conclusion: Supplemental rhIGF-1/BP-3 did not negatively affect clinical values or NEC sensitivity in preterm pigs. Longer-term safety and efficacy of rhIGF-1/BP-3 treatment in preterm newborns remain to be investigated in both pigs and infants.